2023
DOI: 10.3389/fpsyg.2023.1081297
|View full text |Cite
|
Sign up to set email alerts
|

Do you reap what you sow? Driving mechanism of supply chain transparency on consumers' indirect reciprocity

Abstract: IntroductionTo maintain sustainable poverty alleviation in the post-pandemic world, China encourages firms to participate in the “Social Commerce Helping Farmers Project.” This study aims to explore the phenomenon of indirect reciprocity between firms, consumers, and farmers in the supply chain. This study explores how supply chain transparency stimulates indirect reciprocity among consumers through competence trust, goodwill trust, and integrity trust. Furthermore, we explore the impact of compassion and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 224 publications
0
1
0
Order By: Relevance
“…This benign trust also enhances consumers' propensity to make purchases, as they view the producer as reliable and capable of delivering environmentally friendly products that align with their expectations. The conclusion that integrity trust does not play an intermediary factor between information disclosure and purchase intention contradicts the findings of He et al [31]. The inconsistency may be attributed to the fact that integrity trust is closely linked to the commitments and performances of businesses across the entire transaction process.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This benign trust also enhances consumers' propensity to make purchases, as they view the producer as reliable and capable of delivering environmentally friendly products that align with their expectations. The conclusion that integrity trust does not play an intermediary factor between information disclosure and purchase intention contradicts the findings of He et al [31]. The inconsistency may be attributed to the fact that integrity trust is closely linked to the commitments and performances of businesses across the entire transaction process.…”
Section: Discussionmentioning
confidence: 63%
“…Honesty and trust in e-commerce refer to consumers' reliance on online merchants to offer accurate product details and adhere to commitments and transaction regulations. Research has shown that the disclosure of supply chain information can bolster consumers' trust in the competence, integrity, and benevolence of the merchants [31]. The study conducted by Xuhui demonstrated that the information presented by merchants on the platform has a substantial impact on consumers' trust in competence, integrity, and benevolence [32].…”
Section: Stimulus-organism-response Modelmentioning
confidence: 99%
“…Competence trust is a prerequisite for consumers to judge sellers and make purchase decisions ( Fu et al, 2022 ). Supply chain transparency can stimulate indirect reciprocity among consumers by increasing competence trust, benevolence trust, and integrity trust through improved perceived information quality ( He, 2023 ). In online shopping situations, when consumers’ trust in a seller’s competence is established, they tend to trust the seller’s ability to provide safe, quality-compliant products and reliable product information, and these trusts can lead to online purchase behavior.…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%